Availability and chemical associations of cadmium in contaminated tropical soils amended with mineral and organic amendments - Carrillo-Zenteno, Manuel Danilo; Alves-Fernandes, Raphael Bragança; Ferreira-Fontes, Renildes Lucio; Pereira-Jordão, Cláudio (REVISTA TERRA LATINOAMERICANA, 2022)
A study was performed to evaluate the variation in pH, availability, and chemical associations of Cd in two previously contaminated Latosols amended with mineral and organic amendments. The Latosols were contaminated with Cd and amended with vermicompost, sugarcane f ilter cake, palm kernel pie, lime, phosphate rock, or zeolite. Cadmium availability was evaluated monthly in the contaminated soil/soil amendment mixtures with the DTPA and Mehlich-3 extractants for twelve months of incubation. At the end of this period, a sequential extraction procedure was performed in the mixtures to identify the Cd forms present in the several geochemical fractions. Lime immobilized Cd at a larger extension (60%), being the metal transferred to less available fractions. The Mehlich-3 extractant had a high correlation (0.96**) with the available fraction examined by the sequential extraction procedure. In general, organic amendments produced small ef fects on the f inal pH of soil/soil amendment mixtures as compared with the initial soil pH. Mineral amendments caused enhancement of soil pH and the most pronounced ef fect occurred with the use of lime.